Effect of Cathodic Protection on Reinforced Concrete with Fly Ash Using Electrochemical Noise - García Contreras, Jorge; Gaona Tiburcio, Citlalli; López Cazares, Irene; Sánchez Díaz, Guillermo; Ibarra Castillo, Juan Carlos; Jáquez Muñoz, Jesús Manuel; Nieves Mendoza, Demetrio; Maldonado Bandala, Erick; Olguín Coca, Javier; López León, Luis Daimir; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2021)
Corrosion of steel reinforcement is the major factor that limits the durability and serviceability performance of reinforced concrete structures. Impressed current cathodic protection (ICCP) is a widely used method to protect steel reinforcements against corrosion. This research aimed to study the effect of cathodic protection on reinforced concrete with fly ash using electrochemical noise (EN). Two types of reinforced concrete mixtures were manufactured; 100% Ordinary Portland Cement (OCP) and replacing 15% of cement using fly ash (OCPFA). The specimens were under-designed protected conditions (−1000 ≤ E ≤ −850 mV vs. Ag/AgCl) and cathodic overprotection (E < −1000 mV vs. Ag/AgCl) by impressed current, and specimens concrete were immersed in a 3.5 wt.% sodium chloride (NaCl) Solution. The analysis of electrochemical noise-time series showed that the mixtures microstructure influenced the corrosion process. Transients of uniform corrosion were observed in the specimens elaborated with (OPC), unlike those elaborated with (OPCFA). This phenomenon marked the difference in the concrete matrix’s hydration products, preventing Cl− ions flow and showing passive current and potential transients in most specimens.